PENGARUH PEMBERIAN TEMULAWAK PADA LAMBUNG TIKUS YANG MENGALAMI ULKUS PEPTIKUM AKIBAT INDUKSI INDOMETASIN - Indraswari, Cokorde Istri; Kalsum, Umi; Sudjari, Sudjari (Fakultas Kedokteran Universitas Brawijaya, 2004)
ABSTRACT The flavonoid content of Curcuma xanthorriza has an anti inflamatory effect. Inflamation is the basic mechanism in the occurrence of indomethacine induced peptic ulcer. The purpose of this research was detect the effect of the administration of Curcuma xanthorriza decoction in reducing the occurrence of indomethacine induced peptic ulcer. The research methodology used post test control group design. Randomly selected sample of 20 male wistar rat were classified into four groups. Group I (positive control, received 30 mg/kg bodyweight indomethacine), group II (dosage 1, received 30 mg/kg bodyweight indomethacine and 1,3 g/kg bodyweight Curcuma xanthorriza decoction), group III (dosage 2, received 30 mg/kg bodyweight indomethacine and 2,6 g/kg bodyweight Curcuma xanthorriza decoction), and group IV (dosage 3, received 30 mg/kg bodyweight indomethacine and 5,2 g/kg bodyweight Curcuma xanthorriza decoction). Indomethacine and Curcuma xanthorriza was given by intragastric administration. The parameter to be measured was the number of macroscopic gastric hemorrage lesion, because gastric hemorrage is the early manifestation of peptic ulcer. The result of this research was there is a significant difference in the number of macroscopic gastric hemorrage lesion between group I and the other three group (F test, p<0,05), and there is no significant difference for those of group II, III, and IV (F test, p>0,05). Conclusion: Curcuma xanthorriza can reduce the occurrence of peptic ulcer. Key words: Indomethacine, Curcuma xanthorriza, Peptic ulcer, Gastric hemorrage lesion